Collateral Effects of COVID-19: Caring for the Elderly at Home - Matassini, Silvana (2021)
This article discusses the collateral effects of COVID-19 concerning the care of the elderly population who belong to the social security of Peru (EsSalud) and who were confined to their homes. A case study was conducted on the effect of the pandemic in older adults who used to attend an elderly care center (CAM). Semi-structured interviews were carried out via the telephone with the participants. The study showed that the pandemic caused changes in their homes and dynamics. PAMs are supported and cared for by their closest relatives, usually those who share the same household. However, weaknesses in the health system and social protection work could significantly harm this population group with less robust support networks. The main side effects of the pandemic in the PAM are related to their recreational activities since they have been paralyzed, causing feelings of frustration and boredom. The current pandemic still requires constant care and safety to avoid putting the general population at risk. However, it is crucial to consider the effect of the social isolation on people’s health. Joint work between the insured, families and EsSalud will guarantee better prevention and care strategies.